Social and Financial Outcomes of Living Liver Donation: A Prospective Investigation Within the Adult‐to‐Adult Living Donor Liver Transplantation Cohort Study 2 (A2ALL‐2). Issue 4 (10th November 2016) - DiMartini, A.; Dew, M. A.; Liu, Q.; Simpson, M. A.; Ladner, D. P.; Smith, A. R.; Zee, J.; Abbey, S.; Gillespie, B. W.; Weinrieb, R.; Mandell, M. S.; Fisher, R. A.; et al.
Abstract : Because results from single‐center (mostly kidney) donor studies demonstrate interpersonal relationship and financial strains for some donors, we conducted a liver donor study involving nine centers within the Adult‐to‐Adult Living Donor Liver Transplantation Cohort Study 2 (A2ALL‐2) consortium. Among other initiatives, A2ALL‐2 examined the nature of these outcomes following donation. Using validated measures, donors were prospectively surveyed before donation and at 3, 6, 12, and 24 mo after donation. Repeated‐measures regression models were used to examine social relationship and financial outcomes over time and to identify relevant predictors. Of 297 eligible donors, 271 (91%) consented and were interviewed at least once. Relationship changes were positive overall across postdonation time points, with nearly one‐third reporting improved donor family and spousal or partner relationships and >50% reporting improved recipient relationships. The majority of donors, however, reported cumulative out‐of‐pocket medical and nonmedical expenses, which were judged burdensome by 44% of donors. Lower income predicted burdensome donation costs. Those who anticipated financial concerns and who held nonprofessional positions before donation were more likely to experience adverse financial outcomes. These data support the need for initiatives to reduce financial burden. Abstract : Prospective surveys of 271 living liver donors across nine transplant centers show a majority of donors experience improved relationships postdonation, but nearly half had negative financial outcomes, including 44% with out‐of‐pocket donation‐related expenses they considered burdensome.